COVID-19 Vaccine for Elderly: Should We Be Reactive or Proactive? - Setiati, Siti; Marsigit, Jessica (Acta Medica Indonesiana, 2021)
It has been a year since the Indonesian government announced its first COVID-19 identified in Jakarta. Since then, there have been more than 900,000 cases in Indonesia with case fatality rate (CFR) of 2.9%. The number of new cases per day is now ranging from 9,000 cases to almost 13,000 cases. Not only in Indonesia, but the number of new cases along with the mortality rate in other countries, such as Malaysia, Japan, United States, and Europe region also increased dramatically. COVID-19 vaccines are being investigated and the world hopes that vaccines will be the answer to tackle this pandemic. Is it really so? Immunization is an effort to induce immunity in individuals to prevent a disease or the complication related to the diseases that may be catastrophic. Immunization can be divided into passive, which is by giving certain type of antibody and active, which means that either we get the disease, or we get the antigen injected into our body. Having prior vaccination or past COVID-19 does not mean that someone is totally immune to COVID-19 as a recent study suggested that the antibody related to COVID-19 past infection is significantly decreasing after 3 months post-infection. Compliance to implementation of health protocol remained the most crucial strategy during this pandemic.